Managing Liberalization and Globalization in Rural China: Trends in Rural Labour Allocation, Income and Inequality - Dong, Xiao-Yuan; Bowles, Paul; Chang, Hongqin (Global Labour Journal, 2009)
China’s integration into the global economy, while rapid, has been managed as part of a wider liberalization process. The structural changes in the rural economy arising from these twin processes have led to widening intra-rural inequalities. To address these, the central leadership has, in Polanyian manner, moved to counter some of the adverse effects of liberalization and globalization. We discuss this dynamic as it has affected rural China. We analyze results from a national data set covering the period 1991-2006 to assess the extent to which the state has been successful in protecting society from the advance of market forces. We find positive outcomes in terms of real earnings growth and poverty reduction but negative outcomes in terms of the rise in open unemployment and in terms of increasing intra-rural income inequality, although this was noticeably more pronounced in the 1991-2000 period than in the 2000-2006 period when more active government redistributive mechanisms were in place.
Economics
Keywords: globalization; income inequality; labor studies; labour allocation; labour studies; liberalization; rural China

The Athenian Economy in Light of the Welfare State: Karl Polanyi's Work in Perspective - Wjuniski, Bernardo Stuhlberger; Fernández, Ramón García (Journal of Economic Issues (Taylor & Francis Ltd), 2009)
Karl Polanyi considered that the relationship between the markets and their societies was a central feature of any social order. He studied what he called "ancient societies," to compare them with his own times, in an effort to understand that subject This paper aims to show, following Polanyi's work on Classical Greece, that it is possible to make a clear analogy between the Athenian state and economy with the modern Welfare State. First, we present Polanyi's study of the early Athenian economy, focusing on the coexistence of a kind of state economic planning and a market Second, we show how this relates to Polanyi's emphasis in the comparison of different societies and times. Third, we characterize the contemporary Welfare State to make an analogy between these two forms of economic organization. We conclude by underlining the relevance of this analogy in understanding the societies of today.
Economics; Anthropology
Keywords: Athenian supremacy; Greece; 479-431 B.C.; Athens (Greece) - history; Greece; Polis (the Greek word); classical Greek economy; economic anthropology; economic policy; embeddedness; equity; history of economics - to 1800; imperialism; markets - social aspects; money; social order; welfare state

Relaxing the shackles: The invisible pendulum - Stewart, Frances (Journal of International Development, 2009)
This note draws on Polanyi's pendulum in economic policies presented in the the Great Transformation—with swings back and forth between strong restrictions on the market and market domination, each resulting from excesses of the dominant model. The swing he described, when he wrote, was a reaction to the consequences of market domination, notably the Great Depression, and ushered in Keynesianism and the welfare state. In the late twentieth century, there was a swing back towards the market as a result of the inefficiencies associated with this interventionism. This note argues that the pendulum is swinging again, following the political and economic consequences of this market domination. Again market forces are being restrained by regulation, state takeovers, social protection and Keynesian macro-policies, while environmental factors have added to pressures for interventionist policies. Copyright © 2009 John Wiley & Sons, Ltd.
Development Studies; Economics
Keywords: Polanyi; interventionism; markets; pendulum

Paper assets, real debts: An ecological‐economic exploration of the global economic crisis - Kallis, Giorgos; Martinez‐Alier, Joan; Norgaard, Richard B. (Critical perspectives on international business, 2009)
Purpose – This paper sets out to investigate the potential contribution of the inter‐disciplinary field of ecological economics to the explanation of the current economic crisis. The root of the crisis is the growing disjuncture between the real economy of production and the paper economy of finance. Design/methodology/approach – The authors trace the epistemological origins of this disjuncture to the myths of economism – a mix of academic, popular and political beliefs that served to explain, rationalise and perpetuate the current economic system. Findings – The authors recommend ending with economism and developing new collective and discursive processes for understanding and engaging with ecological‐economic systems. Originality/value – The authors embrace the notion of sustainable de‐growth: an equitable and democratic transition to a smaller economy with less production and consumption.
Economics; Business
Keywords: commodification; commodification of nature

An Introduction to Destructive Coordination - Vahabi, Mehrdad (American Journal of Economics and Sociology, 2009)
Polanyi (1944, [1957]1968) has distinguished three “patterns of social integration,” namely, “reciprocity,”“redistribution,” and “exchange.” This triad has provided the starting point for most subsequent discussion. Our purpose is to introduce a further type of coordination, the “destructive mode of coordination.” This mode achieves coordination by intimidation, threat, and the use of non-institutionalized coercive means. Resources and human efforts are allocated in order to appropriate what other people produce. Two simple examples provide an introductory illustration: traffic circles (roundabouts) and prisons. Appropriation through pirating provides a further example of destructive coordination. More specifically, biopiracy (blood patenting) is discussed in order to clarify the relationship between destructive coordination and the institutionalization of property rights. Finally, we focus on the role of destructive coordination as a transitional mechanism that is supported by the institutional vacuum, ultimately yielding to other modes of coordination.
Economics; Sociology
Keywords: appropriation; destructive mode of coordination; social integration

The Social Economics of Neoliberal Globalization - Stanfield, James Ronald; Carroll, Michael C. (Forum for Social Economics, 2009)
The recent period of intensive and extensive development of global economic integration, or globalization, has reached a crossroads. The regime of the neoliberal Great Capitalist Restoration is not sustainable and fundamental governance changes must be made. This paper adds perspective to the choices that must be made at this critical juncture of the global social economy by applying the master concepts of Schumpeter's Creative Destruction and Polanyi's Protective Response.
Economics
Keywords: capitalist systems: political economy; global social economy; international economic order; protective response; social economy

Keynes’s Stimulus, Polanyi’s Movement - Milberg, William S. (Harvard College Economic Review, 2009)
The foundations of Keynes and the principles of Polanyi offer insight into crafting a new American economy
Economics
Keywords: KEYNES; John Maynard; 1883-1946; economics

The Financialization of Modern Economies in Monetary Circuit Theory - Pilkington, Marc (The Political Economy of Monetary Circuits: Tradition and Change in Post-Keynesian Economics, 2009)
Economics
Keywords: Canada: 1913-; banks; depository institutions; economic history: financial markets and institutions: United States; government and the monetary system; haute finance; history of economic thought: individuals; household saving; international financial markets; micro finance institutions; monetary policy; central banking; and the supply of money and credit; monetary systems; mortgages; payment systems; personal finance; regimes; standards

Second thoughts: on economics, sociology, neoliberalism, Polanyi's double movement and intellectual vacuums - Piore, Michael J. (Socio-Economic Review;2009, Vol. 7 Issue 1, p161, 2009)
The article presents a presidential address by Michael J. Piore, delivered at the Society for the Advancement of Socio-Economics (SASE) Annual Meeting 2008 in San José, Costa Rica, in which he discussed the relationship between sociology and economics, and the role that this relationship plays at the current political juncture in the transition from neoliberalism to the formation of public policy.
Sociology; Economics
Keywords: double movement; economic sociology; neoliberalism

The Great Transition - Spratt, Stephen; Simms, Andrew; Neitzert, Eva; Collins, Josh-Ryan (New Economics Foundation, 2009)
Maps out a set of solutions to various systemic problems "This report argues that nothing short of a Great Transition to a new economy is necessary and desirable, and also possible. " - We have called the process by which this could happen the Great Transition as a deliberate echo of The Great Transformation, written by Karl Polanyi in the 1940s.1 While in a relatively short report such as this we could not hope to achieve anything remotely comparable to Polanyi’s great work, the scale of the change we need to see is at least the equal of the changes he described. Polanyi analysed how market processes in the industrial revolution had created severe ruptures in the fabric of social life, and argued strongly that we needed to reverse this and nd a balance between the market and the non-market; the private and the public; the individual and the community. We couldn’t agree more, and the need to achieve this is all the more pressing now given the huge environmental problems we face, problems that Polanyi could not have foreseen in 1944 when the world was caught in the bloody conclusions of the Second World War. The most pressing problem facing humanity now is how to share scarce planetary resources in ways that are just, sustainable and support the well-being of us all.
Economics
Keywords: environemntal politics; environmental value; redistribution